KONVERGENSI STANDAR AKUNTANSI DAN DAMPAKNYA TERHADAP PENGEMBANGAN KURIKULUM AKUNTANSI DAN PROSES PEMBELAJARAN AKUNTANSI DI PERGURUAN TINGGI INDONESIA - Efraim Ferdinan Giri (Jurnal Pendidikan Akuntansi Indonesia, 2008)
Year 2008 is year plan for DSAK for adopting fully all standard which will be invited byIASB. Since 2005, more than ten new and revised accounting standards released by IASB.IAI-DSAK needs more effort to compliance with FASB. Many new knowledge topics willbe transferred to our student. This need reform to accounting learning approach inIndonesia. There is a need to develop a framework for accounting education that consistentbut flexible to accommodate the majority of the accounting educational needs. Mosteducators recognize that only one accounting curriculum is insufficient to meet the need ofvariety of constituents. Therefore, it is essential to adopt an appropriate general frameworkfor coursework is adopted to address the development of many diverse accountingprograms.